A comparative study: epistemology and theology of Ibn al-ʿArabī and Ibn Taymiyya - Kaya, Emrah (2016)
This thesis explores the epistemology and theology of a Sufi theorist Ibn al-ʿArabī (d. 1240) and one of the most controversial Muslim scholars Ibn Taymiyya (d. 1328) comparatively. Although scholars have long emphasized the differences between these two influential and significant figures, the purpose of this thesis is to focus on their potential similarities. The present work at the outset shows that both Ibn al-ʿArabī and Ibn Taymiyya regard revelation, the human intellect, and inspiration – unveiling (ilhām – kashf) to be the main epistemological means for acquiring religious knowledge. However, they differ over the relative value of these means or tools. Both Ibn al-ʿArabī and Ibn Taymiyya place revelation at the top of the hierarchy, but after that Ibn al-ʿArabī places inspiration – unveiling ahead of reason while Ibn Taymiyya reverses the order. The other main subject elaborated in this thesis is the theological issue of the divine names and attributes. This subject is connected to many other theological problems, and both Ibn al-ʿArabī and Ibn Taymiyya pay considerable attention to it. Just as many similar approaches, ideas, and interpretations may be seen concerning their epistemological stances, it is possible to see similarities in their theological positions although there are crucial distinctions as well. The unique way of finding out this similarity is to keep in mind the existence of the duality found in the thought and expression of Ibn al-ʿArabī. Briefly, the main finding of the thesis is that Ibn al-ʿArabī and Ibn Taymiyya are more similar in their epistemologies and theologies than many scholars have thought. They are benefitting from the same epistemological means while putting them in different order. Also, they share similar theological points concerning the divine names and attributes, creation, the divine will, and the incomparability of God while expressing them through different conceptions and styles.